2015
DOI: 10.1177/0956797615605818
|View full text |Cite
|
Sign up to set email alerts
|

Put Your Imperfections Behind You

Abstract: People often fail to muster the motivation needed to initiate goal pursuit. Across five laboratory experiments, we explore when people naturally experience enhanced motivation to take actions that facilitate goal pursuit and why certain days are more likely to spur goal initiation than others. We provide causal evidence that emphasizing a temporal landmark marking the beginning of a new time period increases people’s intentions to initiate goal pursuit. In addition, we propose and show that people’s strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Fresh-start framing. Both laboratory and field research suggests that there are predictable moments when people are especially motivated to make self-controlled decisions (Dai et al, 2014;Dai, Milkman, & Riis, 2015). One class of such moments arises at the beginning of new cycles (e.g., the start of a new week or year, following a birthday or holiday).…”
Section: Other-deployed Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh-start framing. Both laboratory and field research suggests that there are predictable moments when people are especially motivated to make self-controlled decisions (Dai et al, 2014;Dai, Milkman, & Riis, 2015). One class of such moments arises at the beginning of new cycles (e.g., the start of a new week or year, following a birthday or holiday).…”
Section: Other-deployed Interventionsmentioning
confidence: 99%
“…One class of such moments arises at the beginning of new cycles (e.g., the start of a new week or year, following a birthday or holiday). These so-called fresh-start moments facilitate the attainment of long-term goals because they help people feel disconnected from their past failures, which elevates their current self-image and confidence (Dai, Milkman, & Riis, 2015).…”
Section: Other-deployed Interventionsmentioning
confidence: 99%
“…People sometimes show enhanced sensitivity to value around salient yet functionally meaningless points (Allen, Dechow, Pope, & Wu, 2016;Dai, Milkman, & Riis, 2014, 2015Pope & Simonsohn, 2011). For example, people increase donations closer to a mark of a round number (Pope & Simonsohn, 2011), and workers speed up before a break.…”
Section: Arbitrary Anchors As Reference Pointsmentioning
confidence: 99%
“…1 Well-designed reminders can increase adherence, 2 but when should reminders be sent to maximize impact? Prior observational studies 3 and laboratory experiments 4 have shown that engagement in healthy activities increases considerably following “fresh-start” dates—life and calendar events signaling the beginning of new cycles (e.g. birthdays or New Year’s).…”
Section: Introductionmentioning
confidence: 99%
“…birthdays or New Year’s). 3,4 Extending this insight, we conducted the first randomized controlled trial (RCT) examining whether sending medication adherence reminders around fresh-start dates and highlighting these dates as an opportunity for positive changes could boost reminders’ effectiveness.…”
Section: Introductionmentioning
confidence: 99%